DNA methylation profiling is a method of choice for molecular verification of pediatric WNT-activated medulloblastomas - Korshunov, Andrey; Sahm, Felix; Zheludkova, Olga; Golanov, Andrey; Stichel, Damian; Schrimpf, Daniel; Ryzhova, Marina; Potapov, Alexander; Habel, Antje; Meyer, Jochen; Lichter, Peter; Jones, David T. W.; et al. (Neuro-Oncology, 2019)
AbstractBackground. Wingless-activated medulloblastoma (WNT MB) represents a well-characterized molecular variant accounting for 10-15% of all MB and is associ